Spooky witch's guessing game - Miller, Edward (New York Random House Children's Books, 2022)
A Halloween-themed interactive board book that invites readers to guess what the spooky witch is thinking of based on clues.
Cover title.
Ages 0-3.
Grades K-1.
112443
Keywords: Board books; Halloween -- Fiction; Witches -- Fiction; Guessing games; Board books; Fiction; Juvenile works